2010
DOI: 10.1007/s10534-010-9350-0
|View full text |Cite
|
Sign up to set email alerts
|

Cu(II): a “signaling molecule” of the mangrove endophyte Fusarium oxysporum ZZF51?

Abstract: We previously reported the isolation of Cu-fusaric acid (Cu-FA) complex from the mangrove endophyte Fusarium oxysporum ZZF51. In this study, we explored the mechanism of Cu-FA production in the strain ZZF51 by comparing with that of another endophyte Fusarium sp. B2, which produced FA but not Cu-FA in the same culture condition. The results allowed us to hypothesize that Cu(2+) may act as a "signaling molecule" to awaken the silent FA biosynthetic genes in ZZF51, inducing intracellular production of FA followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The ability of FA to chelate metal ions, such as iron or copper, has been known for a long time (Lakshminarayanan and Subramanian, 1955;Malini, 1966;Pan et al, 2010;Tamari and Kaji, 1952). In a recent study, FA has been shown to chelate different metal ions, including Fe 21 , Fe 31 , Cu 21 , Mn 21 and Zn 21 (Ruiz et al, 2015;Yin et al, 2015).…”
Section: Effect Of Ph and Nutrients On Fub1 Transcript Levels And Fa mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of FA to chelate metal ions, such as iron or copper, has been known for a long time (Lakshminarayanan and Subramanian, 1955;Malini, 1966;Pan et al, 2010;Tamari and Kaji, 1952). In a recent study, FA has been shown to chelate different metal ions, including Fe 21 , Fe 31 , Cu 21 , Mn 21 and Zn 21 (Ruiz et al, 2015;Yin et al, 2015).…”
Section: Effect Of Ph and Nutrients On Fub1 Transcript Levels And Fa mentioning
confidence: 99%
“…FA has long been known for its ability to chelate metal ions (Lakshminarayanan and Subramanian, 1955;Malini, 1966;Pan et al, 2010;Tamari and Kaji, 1952). However, the regulation of FA biosynthesis by metals has not been studied so far.…”
Section: Chromatin-mediated Regulation Of Fa Productionmentioning
confidence: 99%
“…It has been reported that copper-fusaric acid complexes are biologically relevant as they upregulate fusaric acid production by Fusarium sp (Pan et al 2010). Given that copper chelators are known to induce an undulated notochord phenotype, we infer that the binding of copper by fusaric acid induces this phenotype despite weak affinity measured in vitro (Tilton et al 2006).…”
Section: Resultsmentioning
confidence: 70%
“…and leaf spot pathogens (such as different species of Alternaria) were also recovered from apparently healthy prickly acacia plants. Many of these fungi were also previously reported as being endophytes (Teleha & Miller 2007;Pan et al 2010;Porras-Alfaro et al 2014;Swett & Gordon 2015).…”
Section: Major Findingsmentioning
confidence: 73%